2013
DOI: 10.1021/ic4017883
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides and Quantum Dots as Förster Resonance Energy Transfer Agents for Diagnostics and Cellular Imaging

Abstract: Luminescent lanthanide labels (LLLs) and semiconductor quantum dots (QDs) are two very special classes of (at least partially) inorganic fluorophores, which provide unique properties for Förster resonance energy transfer (FRET). FRET is an energy-transfer process between an excited donor fluorophore and a ground-state acceptor fluorophore in close proximity (approximately 1-20 nm), and therefore it is extremely well suited for biosensing applications in optical spectroscopy and microscopy. Within this cogent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 179 publications
1
108
0
Order By: Relevance
“…The availability of nanoparticles doped with luminescent lanthanide ions or complexes on one hand and of up-converting nanoparticles (UCNPs) on the other hand is presently adding new dimensions to this area of research by expanding it to NIR-NIR imaging, drug delivery and photodynamic therapy of cancer.It is noteworthy that sophisticated multiplex analyses or imaging experiments may require combining two classes of luminophores, e.g. in some FRET experiments, QDs can function as donors[18] or acceptors[19] for LLBs In this review, we attempt to give a broad overview of the applications of lanthanide optical probes in bioanalysis and bioimaging. Main current applications of lanthanides in biology and medicine are in magnetic lanthanide ions are used in radioactive treatment of cancer and they are known to have anticoagulant and antimicrobial properties, but the corresponding uses remain minor.…”
mentioning
confidence: 99%
“…The availability of nanoparticles doped with luminescent lanthanide ions or complexes on one hand and of up-converting nanoparticles (UCNPs) on the other hand is presently adding new dimensions to this area of research by expanding it to NIR-NIR imaging, drug delivery and photodynamic therapy of cancer.It is noteworthy that sophisticated multiplex analyses or imaging experiments may require combining two classes of luminophores, e.g. in some FRET experiments, QDs can function as donors[18] or acceptors[19] for LLBs In this review, we attempt to give a broad overview of the applications of lanthanide optical probes in bioanalysis and bioimaging. Main current applications of lanthanides in biology and medicine are in magnetic lanthanide ions are used in radioactive treatment of cancer and they are known to have anticoagulant and antimicrobial properties, but the corresponding uses remain minor.…”
mentioning
confidence: 99%
“…UCNPs are conjugated with energy acceptors, whose excitation spectra has to overlap with the emission spectra of the NPs. The acceptor can be organic fluorophores [111,144,344,345], fluorescent proteins [346], metallic NPs [341], graphene oxide (GO) [338,339,347,348], carbon NPs [342] and semiconductor QDs [345,349,350]. The working principle of upconversion LRET [depicted in Figure 21(i)] has demonstrated its huge potential through the development of sensing systems for the determination of 17β-estradiol [336], enzymatic activity [351], matrix metalloproteinase [342], mycotoxins [338], ATP [339], IgG [352], glucose [347] and pesticides [353], among others.…”
Section: Biosensing Applicationsmentioning
confidence: 99%
“…Numerous studies have reported both time-gated and steady-state imaging of responsive lanthanide sensors in living cells, including sensors for Zn 2þ , bicarbonate, pH, and singlet oxygen (21)(22)(23)(24). Lanthanide biosensors may be designed as responsive probes that exhibit an analyte-dependent change in emission intensity or lifetime (6), or as FRET-based systems that use Tb(III) or Eu(III) complexes as donors and FPs, organic dyes, or even quantum dots as acceptors (8,25). The lanthanidebased FRET approach can detect interactions between donor-labeled and acceptor-labeled proteins (via a so-called dual-chain biosensor) or conformational changes of a single protein labeled with both a lanthanide donor and a fluorescent acceptor (via a single-chain biosensor).…”
Section: Introductionmentioning
confidence: 99%